Simulação numérica do perfil de microssegregação na solidificação rápida de um sistema Ag-Cu - Trigueiro, Pollyana de Aragão (2013)
A model was used to simulate solute distribution during rapid solidification of a system Ag-15%massCu with initial undercooling of 5 K, 10 K and 30 K. Boettinger et al (1987) measured the microsegregation profile in Ag-Cu alloys superficially treated with a focused electron beam (resolidification). In that work, they found an irregular variation for Cu concentration in cross sections of the resolidified microstructures. In some cases, the profile of concentration versus radius presented a W shape. Current models of microsegregation predict a monotonic variation the concentration depending on the cell radius, which are apparently not in accordance with the acquired measurements. The present study used a numeric model to evaluate the solidification of Ag-Cu alloy under same conditions to the Boettinger´s experiment. Numerical results are for a metallic spherical drop, initially liquid, cooled by convection. Solidification starts in the center of the droplet in a given undercooling. The algorithm used here is based on a model in volumetric average of the quantities and the balance equations in a representative elementary volume for treating a solid/liquid mixture. Inside the droplet transport of energy and mass are repurely diffusive processes of average quantities. The algorithm used permitted a global analysis of the phenomena occurring during the solidification process, as well as a local analysis of the quantities involved, which has been shown to be a prerequisite for the prediction of non-monotonic profiles of microsegregation, such as those measured in the experiment mentioned above.